PELATIHAN HIV/AIDS UNTUK KADER POSYANDU REMAJA ANGGUN NAN TONGGA KOTA PARIAMAN - Mery Ramadani; Yessy Markolinda; Trisfa Augia (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
Adolescents are individuals who are in a transitional stage between childhood and adulthood. This period is known as a critical period in efforts to find identity and is prone to falling into delinquency and bad behavior. One of the potential risky behaviors due to juvenile delinquency is HIV/AIDS. The incidence of this disease increases every year in adolescents. This condition is very worrying, so efforts are needed to suppress the emergence of new cases and also comprehensive management of sufferers. Youth Integrated Healthcare Center can be used as a place to prevent this disease. Youth cadres in each Integrated Healthcare Center need to be formed and trained so that they can become extensions of health workers. Every cadre personnel must be well prepared and equipped with sufficient knowledge. Thus, efforts to prevent this risky behavior can be more widely and massively carried out among adolescents. The purpose of this activity is to provide education to youth regarding HIV/AIDS, prevent bad behavior, and improve adolescent reproductive health. The method used is the pretest and post-test to determine whether there is an increase in adolescent knowledge. The target of the service is teenagers at the Anggun Nan Tongga Youth Integrated Healthcare Center, Pariaman City. From this activity, it can be seen that there was an increase in adolescent knowledge by 75%.